Desenvolvimento de recobrimento de fruta pão e quitosana associada a nanoemulsão de óleo essencial e sua aplicação na conservação pós colheita do mamão “golden” - Penna, Cristiane Rodrigues de Araújo (2018)
The use of biodegradable coatings has been considered as a promising alternative for postharvest fruit conservation. However, studies aimed at the elaboration and application of coatings based on unconventional raw materials associated with nanoemulsion, which effectively promote an increase in the postharvest useful life of fruits with antifungal action are still scarce.The objective of this study was to develop and evaluate the physical, physicochemical and antifungal potential of coatings in the form of bilayers based on breadfruit starch (BFS), chitosan (C), sodium alginate (SA) and fennel essential oil (FEO) and its influence on postharvest conservation of Golden papaya cultivar.The study was carried out in three stages: in the first stage, the extraction of breadfruit starch from fruits harvested at two maturity stages (immature and ripe) was carried out. Starch was evaluated for its chemical characteristics and functional properties. Ripe fruits showed higher yields in the extraction of starch (80.02%), amylose (51.93%) and amylopectin (28.19%), with a degree of gelatinization at 90°C, thus, this was used in the preparation of coatings in bilayers. The second stage was elaborated through experimental planning, for the formulation of the bilayers, evaluating the dependent variables regarding their physical, physicochemical (permeability, opacity, solubility, color, thickness), antifungal (Colletotrichum gleosporioides) characteristics. The bilayer formulations with 2.0% BFS, 0.25; 0.43 and 0.50% FEO, 0.0; 0.50; 0.85% of C and 0.50% SA showed superior physicochemical and antifungal properties. Therefore, in the third step, these formulations were also evaluated for X-ray diffraction, Absorption Spectrometry in the Infrared region with Fourier Transform, Scanning Electron Microscopy and also were applied to Golden cultivar papaya fruits, for evaluation during 12 consecutive days, under room condition (24±2°C e 75% RH). For the application of the bilayers on the fruits, the first layer was applied, then, after complete drying, the second layer was applied. The control formulation was also used, in which there was no application of coatings. Every two days, four plots were taken for physicochemical determinations, bioactive compounds, enzymatic activity, and sensory evaluations, and every day for mass loss and respiratory activity. Bilayer coating was effective in delaying the maturation and inhibiting fungal growth in Golden papaya and, consequently, maintaining its functional potential, especially in fruits coated with the bilayer composed of 0.50% FEO nanoparticles and SA and 2% BFS with 0.50% C, which maintained fruit quality in at least twelve days under room conditions.